(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
Patient’s quality of life (QL) measures are endowed with independent predictive value and these factors are considered to be more distinct than patient’s general somatic condition for predicting patient’s health condition. However, the number of researches devoted to QL prediction in the field of medical science is low. The aim of research is evaluation of predictive measure of QL of early aged children. Prospective observational study was carried out. The objects of the research were 2362 early age children (3months-3years old) from pediatric polyclinics of Yerevan. QL of children was evaluated with the international questionnaire “QUALIN”. Wald’s analytical method has been applied for predictive evaluation of QL criteria and formation of risk group. For the analysis and evaluation of the statistical material used SPSS Statistics software package. In social-hygienic factors more important were: family type, conflicts in family, disabled child and frequent morbidity families, presence of artificial nutrition since birthday. Among medico-biological factors the presence of two or more diseases in neonatal period, low and high levels of physical development, weight deficit and obesity, child’s health group and respiratory, nervous and digestive system diseases were more significant. In terms of predictive evaluation of QL, it can be stated that a number of medico-biological and socio-hygienic factors affect the overall formation of QL. By means of predictive evaluation of QL one can originally set apart targeted risk groups and if the score of predictive evaluation is +13 and higher, implement health measures, which may provide with improvements of QL criteria.